Philosophy and dimensions of national communication policy - Nnaemeka, Tony.; Uvieghara, E. E.; Uyo, Didi.; Centre for Black and African Arts and Civilization (Lagos : Centre for Black and African Arts and Civilisation, 1989)
This provides a representation of essays of leading scholars, administrators and policy planners towards the development of such comprehensive national communication policy
Papers presented at a seminar held Feb. 1-7, 1987, Topo-Badagry, Nigeria.
Includes bibliographical references and indexes.
eej 15/01/2019
Loans
Keywords: Communication policy